The Effect of Abusive Supervision on Employee Creativity: The Mediating Role of Negative Affect and Moderating Role of Interpersonal Harmony - Chen, Lili; Ye, Zhixiao; Shafait, Zahid; Zhu, Hongying (Frontiers in Psychology, 2022)
This study investigates the relationship between abusive supervision and employee creativity by shedding light on the mediating role of negative affect and the moderating role of interpersonal harmony. Based on Affective Event Theory, it was hypothesized that abusive supervision impacts employees’ negative affect and their creativity. Data from a questionnaire survey of 398 Chinese employee–supervisor dyads were collected and analyzed. The results support our hypotheses, address unexplored theoretical predictions, and suggest that organizations should deal with the factors undermining employees’ emotions to improve their creativity.